Transitioning from Natural Conservationism to Sustainable Development: A Shift in Environmental Policy (Global Journal of Human-Social Science, 2023)
Contrasting the conservationist bias of environmental balance with that of sustainable development the author distinguishes the influence of both in the current formulation of environmental policies including trends respectively more regulatory or redistributive as public policies In this sense it highlights the global need to overcome natural conservationism a remnant of the 19th century and whose obsession with the untouchability of nature does not admit the synergies between nature and humanity fundamental to promoting sustainability Which if assumed as a progressive ideology it transcends the left-right differentiation implying broad coalitions both political and socioeconomic so that we become socially ecological
Keywords: sustainability - environmental policies - sustainable development